Acquired auditory neuropathy spectrum disorder after malaria treated with quinine. (July 2020) - Brough, Helen
Auditory neuropathy spectrum disorder (ANSD) can cause significant hearing impairment; it occurs when there is intact outer hair cell function in the inner ear, with a dyssynchronous neural response, thought to be due to dysfunction of the inner hair cells (IHCs), the synapse of the IHCs and the auditory nerve, or of the auditory nerve itself. This case report describes the onset of ANSD in a Malawian child after severe malaria treated with quinine. Diagnosis of ANSD was made by confirming the presence of otoacoustic emissions, together with the absence of auditory brainstem response and absent acoustic reflexes.